2009
DOI: 10.1016/j.neulet.2009.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Localization of COX-1 and COX-2 in the intracranial dura mater of the rat

Abstract: Primary headaches such as migraine can be aborted by systemic administration of non-steroidal antiinflammatory drugs (NSAIDs), potentially through the non-selective inhibition of cyclooxygenase (COX) activity in the intracranial meninges. In this study we have used single and double labeling immunohistochemistry to examine the distribution of the COX-1 and COX-2 isoforms in the intracranial dura mater of the rat and identify cell types that express them. COX-1 immunoreactivity was found in medium and small dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Despite the lack of TNFR1 immunoreactivity in dural axons, we detected its expression in dural blood vessels. Dural vascular TNFR1 expression was also co-localized with vimentin, a marker that identifies dural vascular endothelial cells [47] and is in agreement with its expression on vascular endothelial cells from other tissues [21]. Dural vascular TNFR1 was also co-localized with COX-1 which we have shown recently also localized to dural vascular endothelial cells [47].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Despite the lack of TNFR1 immunoreactivity in dural axons, we detected its expression in dural blood vessels. Dural vascular TNFR1 expression was also co-localized with vimentin, a marker that identifies dural vascular endothelial cells [47] and is in agreement with its expression on vascular endothelial cells from other tissues [21]. Dural vascular TNFR1 was also co-localized with COX-1 which we have shown recently also localized to dural vascular endothelial cells [47].…”
Section: Discussionsupporting
confidence: 70%
“…TNFR1 immunolabeling was predominantly localized to the dural vasculature with medium and small dural blood vessels showing the highest expression. As figure 5 demonstrates, TNFR1 was co-localized in dural vessels with vimentin, indicating its presence in endothelial cells [47]. Vascular TNFR1 was also co-labeled with vascular COX-1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The co-localization of COX-2 and CGRP is observed in some dural nerve fibers, which suggests that COX-2 may be related to the function of CGRP. 39 It has been shown that CGRP release is mediated by a COX-2-dependent pathway and COX-2 expression in trigeminal ganglion cells could contribute to the development of pain in trigeminally mediated headaches. 40,41 The attenuation of CGRP release by COX-2 inhibition could at least in part explain the mechanism of COX inhibitors as migraine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One major process that might contribute to headache triggering is sterile meningeal inflammation and the ensuing persistent activation of primary afferent nociceptive neurons that innervate the meninges and their related large blood vessels. The dural layer of the meninges is the one most heavily innervated by nociceptive afferents and is also highly populated by immune cells, including macrophages, dendritic cells and mast cells (MCs) (4, 5). Dural MCs are of particular interest because of their close proximity to dural nociceptors (6, 7).…”
Section: Introductionmentioning
confidence: 99%